2-Octylaminopyridine assisted solvent extraction system for selective separation of palladium(ii) ion-pair complex from synthetic mixtures and real samples. Issue 6 (21st March 2015) - Suryavanshi, Vishal J.; Pawar, Rupali R.; Anuse, Mansing A.; Mulik, Ganpatrao N.
<x xml:space="preserve">Abstract</x> 2-Octylaminopyridine assisted solvent extraction for selective separation and quantification of palladium(ii) ion-pair complexes from synthetic/real samples is developed.